A morphologic study of unexplained hepatitis following halothane anesthesia. - Wills, E. J. (1978)
A survey of postoperative jaundice throughout the United Kingdom allowed the detailed analysis of 76 patients with unexplained hepatitis following halothane anesthesia ("halothane hepatitis"). In 16 patients liver biopsy specimens were examined by light and/or electron microscopy to determine whether the liver morphology could aid the differentiation between "halothane" and "acute viral" hepatitis. The mitochondrial changes often claimed to be characteristic of holothane hepatitis were unremarkable in our patients. Since lipid vacuolation and a predominantly centrilobular distribution of necrosis are not classically described in fatal viral hepatitis, the presence of these features in some of our fatal cases was of some diagnostic interest. In general, however, the results of light and electron microscopy in patients with unexplained postoperative hepatitis is considered to have little differential diagnositc value.